The value of a translation policy in the management of natural and economic resources in the province of Kongo Central (DRC) : the Parc Marin des Mangroves as case study - Ngoma Toko, Jean Pierre (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023.